TRADING IMPLEMENTATION IN INDONESIA STOCK EXCHANGE, PALEMBANG BRANCH OFFICE ACCORDING TO THE SHARI’AH LAW AND BUSINESS - Romziatussaadah, Romziatussaadah (Universitas Islam Negeri Raden Fatah Palembang, 2020)
As the largest Muslim country in the world, Indonesia is a potential market in the development of the Islamic finance industry. Investment in the capital market, which is part of the Islamic financial industry, has an important role in increasing the market share of the financial industry in Indonesia. Although the development is relatively new compared to sharia banking and sharia insurance, along with the significant growth of the Indonesian capital market industry, it is expected that sharia investment in the Indonesian capital market will experience significant growth. This study aims to explain the trading mechanism on the Indonesian stock exchange that involves Islamic stocks and to find out a review of sharia law and business in the implementation of these trades / transactions. This study uses a normative juridical approach. This research was conducted in Palembang by taking the object on the Indonesia Stock Exchange. Data obtained from in-depth interviews, literature study, and observation. Qualitative analysis can be interpreted as an explanation and interpretation in a logical, systematic and consistent manner. In connection with this, the techniques used and the nature of the data obtained from the results of their collection, can be analyzed using taxonomic analysis. This study concludes that 1) the capital market in Indonesia is categorized into two, namely a) conventional capital markets and b) Islamic capital markets; 2) The regulation regarding the Sharia capital market is so complete by the capital market in Indonesia. Starting from the Capital Market Law, the DSN MUI and BAPEPAM fatwas; and 3) The operational mechanism of the Sharia Stock Exchange has been clearly implemented and regulated in these regulations. So that capital market players already understand things that are appropriate and not in accordance with Sharia.